DEVELOPMENT OF APPROPRIATE MEDIA TO IMPROVE THE QUALITY OF LIFE FOR THE ELDERLY PEOPLE BY THE PARTICIPATION PROCESS IN KLONG LADPRAO COMMUNITY, BANGKOK - สมพืช ปรียา; หรุ่นเกษม นิษฐา (Academic Journal Phranakhon Rajabhat University, 2020)
This research aims to study a healthcare information exposure of elderly lining in Ladprao canal community. By trying to evaluate their satisfaction on healthcare media, the research utilizes questionnaire, media evaluation form, and satisfaction evaluation form on population from elderly living among 50 communities around Ladprao canal community. Average and standard division are methods used in data analyzation. This study finds that 1. a healthcare manual, concerning diet, exercise and mental health in A4 size is the most suitable match with populations’ media exposure. 2. populations prefer font TH Krub due to its sharpness, also they prefer a heading in font size 70 point, a title in font size 30 point, and a text body in font size 20 point for its clarity. 3. populations highly satisfy in the healthcare manual as it gains average of 4.36 in satisfaction scale.